Pengaruh Latihan Circle Passing dan Y Passing Pattern Terhadap Akurasi Passing Pemain Sepak Bola SSB Mitra Sampangan U-12 - Vicky Tri Firmansyah; Martin Sudarmono; Mohamad Annas; Fery Darmanto (Indonesian Journal for Physical Education and Sport, 2024)
This study aims to determine the effect of Circle Passing and Y Passing Pattern training on the passing accuracy of SSB Mitra Sampangan U-12 players. This type of research is quantitative research with experimental methods. The design of this research is "two group pretest post-test design". The population and sample in this study were all SSB Mitra Sampangan U-12 players totaling 20 people. Sampling in this study was done with total sampling technique. The data analysis technique used in this study is the T test using SPSS 25. The results stated that there was an increase in mean of the passing test after the implementation of Circle Passing and Y Passing Pattern training. The Circle Passing training group has a pretest average value of 5.10 and a posttest average value of 6.60 with a percentage increase of 29% and Y Passing Pattern training has a pretest average value of 4.90 and a post-test average value of 6.70 with a percentage increase of 36%. Based on the results of the research data, it can be concluded that Circle Passing and Y Passing Pattern exercises both have an influence on the passing accuracy of the players. Y Passing Pattern training is better than Circle Passing training on the passing accuracy of SSB Mitra Sampangan U-12 players